(untitled) (Voice of Teacher, 2021)
The paper aims to explore decision making role of women in household chores that is cooking, dressing and caring of the children and other household activities. This study applied the semi-structured interview with case studies and observation method for the exploration of grounded realities of decision-making practices at household chores. Upon examination of everyday work situation, it becomes clear that the status of women in household chores is meaningful in Nepalese society; however there have been tremendous changes over the generations due to the several socio-political and economic shifts. Empirical observation and informations from the field study prevailed that role of decision making of women seems to be dominant in cooking, washing and cleaning at the same time their roles in political participation, income and purchasing activities also to be peripheral. The role of women in the household’s level have been transforming along with their age and marital status; for instance, teenager women prefer official jobs whereas, mature women discourage official jobs and public activities. The women, who engaged in the public jobs equally contributes in the household chores. The concerned authorities have not paid due attention to the plight of these simple hard working labourers who has made significant contribution towards increasing gross national product and also earning for their family.